Comparative evaluation of root canal transportation and centering ability in curved mesiobuccal canals of mandibular first molars after instrumentation with different file systems-An In vitro study - Akshayraj Langaliya; Anjali Kothari; Aastha Buch; Riya Dave; Jinali Shah; Nishtha Shah (Wolters Kluwer Medknow Publications, 2023)
Aim: To assess the canal transportation and centering ability in the mandibular first molars' curved mesiobuccal canals after instrumentation with file systems XP endo Shaper, self-adjusting File (SAF), Hyflex EDM, Pro Taper NEXT, WaveOne Gold, and K files with the help of Cone-Beam Computed Tomography (CBCT). Materials and Methods: Ninety recently extracted mandibular first molars with mesiobuccal roots that had a 25-30 degree canal curvature were assessed. Following preoperative CBCT scans, teeth were allocated randomly to six experimental groups of fifteen. After preparation with XP endo Shaper, SAF, Hyflex EDM, Pro Taper Next, WaveOne Gold, and K files, post-instrumentation scans were taken using same parameters as pre operative scans. At 3 mm, 6 mm, and 9 mm from the apex, samples were assessed for canal transportation and centering ratio. Results: Apical transportation was least for XP endo Shaper as compared to other groups except SAF and the results were statistically significant. K file showed the highest apical transportation toward the lateral wall of the root canal. XP endo Shaper was better in maintaining centering ability of middle and apical third of canal and SAF was better in maintaining centering ability of coronal third. Conclusion: In root canal preparation, least apical transportation and better centering ability with XP endo Shaper than other file systems compared. K file showed the highest transportation.